Getting on better with teenagers : improving behaviour and learning through positive relationships - Dixie, Gererd (Continuum International Pub. Group, 2011)
With clear guidance and advice from the viewpoint of a seasoned teacher and trainer, Getting on Better with Teenagers explains how building a better rapport with your class can support students' academic, social and personal development, as well as improving behaviour issues. This practical guide contains end-of-chapter summaries and suggestion boxes, so you can try out the techniques straight away. Being a successful form tutor requires you to be a key point of contact for those students in need of adult help and advice.